ERASURE DAN SILENCE LINGKUNGAN DALAM AWIG-AWIG DESA ADAT DENPASAR - I Putu Permana Mahardika; Reilind Brigitta Lee Maharani; Rona Bassama (Universitas Warmadewa, 2026)
Balinese customary regulations (awig-awig) are often assumed to be ecological because they rest on Tri Hita Karana, especially the element of palemahan. This assumption flattens every kind of environmental absence into a single form, yet absence takes more than one form. Some natural entities are named but reduced; others are never raised at all. Reading the awig-awig of Desa Adat Denpasar, this study separates the two, known in ecolinguistics as erasure and silence. The analysis is qualitative, drawing on Stibbe's erasure and salience and Huckin's typology of silence, and weighs its findings through an ecosophy that joins Tri Hita Karana with the principle of sustainability. Land, plants, animals, and water appear mainly as property, boundaries, or things to be discarded, and water in particular figures only as waste and as danger. Meanwhile, the water pollution and urban waste that trouble Denpasar go unregulated. Palemahan ends up meaning the ordering of owned space more than the care of an environment. The presence of Tri Hita Karana in a text does not guarantee a genuinely ecological outlook.